LEGAL ASSISTANCE IN THE PROCESS OF LICENSE EXTENSION OF REGIONAL BP LICENSING AT PT KARYA SUKSES PERSADA - Nadia Salsabilla; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
Karya Sukses Persada is a company engaged in construction services, construction services are a consulting service for construction services, planning for construction, working on an construction project as well as services for construction supervisors. The company is working on a project that must deliver goods from Batam to Tanjung Pinang therefore it requires a Business Permit for the Regional Concession Agency. To obtain a Batam Business License, the author uses direct interview techniques with sources, namely public service officers and also HRD managers from partner companies, then the technique used is observation technique. Then the output achieved from this project is the issuance of a Regional BP Business License for PT Karya Sukses Persada which is needed by partner companies.